Evaluasi Kesesuaian Lahan Berbasis SIG Untuk Tanaman Cengkih, Pisang, dan Ubi Kayu di DAS Wai Ela, Negeri Lima, Pulau Ambon - Hatulely, Gresi; Haumahu, J P; Osok, Rafael M; Talakua, Silwanus (JURNAL BUDIDAYA PERTANIAN, 2021)
The characteristics and quality of land resources are important things that must be considered in the planning, utilization and management of land for agricultural purposes. The purposes of this research were to describe land characteristics and quality, and to determine the suitability class, subclass, and limiting factors for clove (Zysygium armoticum), banana (Musa sp), and cassava ( Manihot esculenta Crant.) crops in Wai Ela Watershed. The method used in this study was a survey with land units as a fieldwork map which resulted from overlying four components, namely slope class, lithology formation, soil, and land uses. Field data collection was conducted following the observation lanes at 15 selected sample areas representing 72 land units. Data analysis was carried out by using a geographic information system (GIS), involving: (1) SRTM image analysis to produce topography class, (2) maps overlay to produce land units, and (3) attribute data processing to produce land suitability class. The study results showed that the land suitability for clove consisted of the suitable class of S2 (21.91 ha) and S3 (327.89 ha), and not-suitable, N (1069.85ha), with limiting factors being flooding, soil depth, and slope steepness. Land suitability for bananas consisted of the suitable class of S3 (501.70 ha), and not-suitable, N (686.99 ha) with limiting factors being flooding, erosion, and slope steepness; whereas land suitability for cassava consisted of the suitable class of S3 (501.70 ha) and not-suitable, N (917.96 ha), with limiting factors being flooding, slope steepness, and erosion.